Islamic Religious Education Management Through the Role of Tahfidz Teachers in Improving Students' Al-Qur'an Memorization Abilities - Arifin, Muh; Wajdi, Farid; Putra, Zulfikar (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to determine the management of Islamic education through the role of tahfidz teachers in improving the ability to memorize the Qur'an. The type of research used is qualitative research with a field approach. The data sources for this study are tahfidz teachers, female students, and monthly memorization sheets of female students. Furthermore, the data collection method uses observation, interview, and documentation techniques. The data processing and analysis method is carried out through three stages: data reduction, data presentation, and conclusion. Based on the results of the study, the role of tahfidz teachers in improving the memorization ability of female students at SMP TQ Muadz bin Jabal Konawe Selatan is: providing motivation to female students, improving female students' reading of the Qur'an before memorizing, using the tahsin and tahfidz methods, telling inspiring stories and providing shows about successful memorizers of the Qur'an, guiding female students to continue muroja'ah, giving sanctions to female students, and conducting evaluations.